Handbook of research on pathophysiology and strategies for the management of COVID-19 - El Hiba, Omar, 1985-; Radhakrishnan, Jayakumar; Balzano, Tiziano, 1988-; Isbaine, Faical, 1986- (Advances in medical diagnosis, treatment, and care (AMDTC) book series., 2022)
"The book provides recent and updated evidences on the management of COVID-19 through the medical and vaccination approaches, covering different sides of the disease in association with effects on the physiological functions of the human body "--